2021
DOI: 10.3390/s21020355
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Flow Meter by Fiber-Optic Sensing of Heat Propagation

Abstract: Monitoring fluid flow rates is imperative for a variety of industries including biomedical engineering, chemical engineering, the food industry, and the oil and gas industries. We propose a flow meter that, unlike turbine or pressure-based sensors, is not flow intrusive, requires zero maintenance, has low risk of clogging, and is compatible with harsh conditions. Using optical fiber sensing, we monitor the temperature distribution along a fluid conduit. Pulsed heat injection locally elevates the fluid’s temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…One dimensional combined transient energy equation is mentioned as follows [30]. (6) Where 𝜌 is density, cp specifies heat under constant pressure, T is temperature, t is time, K is thermal conductivity, 𝑄 𝑟 ̇ shows gradient heat flux vector and the divergence of radiative heat flux in ( 6) is the net radiant energy emitted from a unit volume. It is a scalar quantity, a function of position, and is called a radiative source where Eq.7 present it.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One dimensional combined transient energy equation is mentioned as follows [30]. (6) Where 𝜌 is density, cp specifies heat under constant pressure, T is temperature, t is time, K is thermal conductivity, 𝑄 𝑟 ̇ shows gradient heat flux vector and the divergence of radiative heat flux in ( 6) is the net radiant energy emitted from a unit volume. It is a scalar quantity, a function of position, and is called a radiative source where Eq.7 present it.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Beyond these activities, the transmission medium’s production was stopped for a few years because of the lack of commercial field claims. Composite fiber has various applications, such as light transmission sensing, data transmission for optical signals, and deformation detection, which is used in solid mechanical experimental research and chemical sensing [ 3 , 4 , 5 , 6 ]. Their applications are critical because they have improved the reliability of electrical machines, ICs, and microelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…Considering various sensors, such as temperature and airflow virtual sensors, the suggested method is examined on a real building in Denmark, and it is shown that abnormal oscillation in temperature is strongly detected. In [10], a fiber-optic approach is introduced, and its accuracy and maintenance cost is studied. The variance shift scheme is formulated in [11] to construct an FD method for a navigation system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Controlling fluid flow requires constant flow monitoring and the measurement of flow rates [1][2][3]. Problems that occur in flow meters can cause product quality and efficiency to decrease.…”
Section: Introductionmentioning
confidence: 99%